2008
DOI: 10.1021/ol800988w
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorophores Containing Benzo[c]heterocycle Subunits

Abstract: The syntheses and spectroscopic properties of eight new push-pull type near-infrared fluorophores that contain either isobenzofuran or isothianapthene subunits are presented. The isobenzofuran dyes demonstrate significantly red-shifted absorption from their isothianaphthene counterparts, which is attributed to isobenzofuran's more potent pro-quinoidal character.In vivo near-infrared (NIR) fluorescence imaging is rapidly emerging as a powerful diagnostic method. 1 In the NIR region (650-900nm) biological chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…813 Push-pull-type fluorophores comprising MeO-, HO-, and Me 2 N-groups as donor and dicyanovinylene as acceptor were synthesized as NIR contrast agents for biomedical applications. 814 Hong et al synthesized two air-stable p-type organic semiconductors, which have a symmetrically substituted 2,7-divinylbenzothieno[3,2-b]benzothiophene backbone. They showed good electrical performances on a SiO 2 /Si substrate and high field-effect mobilities up to 0.4 cm 2 V -1 s -1 .…”
Section: Appendixmentioning
confidence: 99%
“…813 Push-pull-type fluorophores comprising MeO-, HO-, and Me 2 N-groups as donor and dicyanovinylene as acceptor were synthesized as NIR contrast agents for biomedical applications. 814 Hong et al synthesized two air-stable p-type organic semiconductors, which have a symmetrically substituted 2,7-divinylbenzothieno[3,2-b]benzothiophene backbone. They showed good electrical performances on a SiO 2 /Si substrate and high field-effect mobilities up to 0.4 cm 2 V -1 s -1 .…”
Section: Appendixmentioning
confidence: 99%
“…In other cases, the incorporation of furans led to materials with properties superior to those containing thiophenes. Meek and coworkers found that the use of IBFs over isothianapthenes (ITNs) led to improved dyes for near-infrared (NIR) fluorescence imaging [15]. Likewise, recent studies on oligofurans show better solid state and optical properties as compared to oligothiophenes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Emission values of the naphtho[c]thiophenes clearly indicated that they can be explored Far-IR fluorophore applications. 16 Research is in progress to synthesize push-pull systems involving naphtho[c]thiophene unit.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, Swager and co-workers reported the synthesis of push-pull-type near-IR fluorophores containing isobenzofuran and isothianaphthene subunits. 16 Cava and co-workers reported the synthesis and electropolymerization of 1,3-dithienylnaphtho[c]thiophene 3. 17 Even after fifteen years of this first report, with the exception of parent naphtho[c]thiophene 18 till date any further derivative of isothiaanthracene (ITA) is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%